Visualisasi Data Malnutrisi Anak Di Asia Menggunakan Looker Studio Serta Analisis Data Dengan Metode ANOVA - Yeni Setiani; Nabila Rachmah; Indra Purnama (Lembaga Pengembangan Kinerja Dosen, 2023)
Child malnutrition is a serious problem involving complex factors in various countries. The level of the economy in a country is one of the factors that influences the occurrence of this problem. Using data obtained from the data UNICEF site on Child Malnutrition, this study involved processing the data to create a data visualization in the form of a dashboard. This dashboard is able to provide information on the prevalence of child malnutrition and its geographic distribution patterns in the Asian region by utilizing the Looker Studio platform. In addition, this study was also conducted to analyze the effect of state income classification on the percentage of child malnutrition that occurs. The use of the ANOVA analysis method in this study is the basis for answering research questions related to analysis. The stages carried out in this study were Data Collection, Data Preprocessing, data analysis using the ANOVA method, and data visualization. The result of this study is a data visualization in the form of an informative dashboard, as well as the results of the analysis showing that there is a significant effect of the classification of state income on the percentage of child malnutrition in that country. This study provides important insights into the problem of child malnutrition in Asia in a visual form and provides results of statistical significance, indicating that there is a significant relationship or influence between the classification of national income and the percentage of child malnutrition that occurs in that country, not just a coincidence.